THE NIGERIA POLICE FORCE AND THE CRISIS OF LEGITIMACY: RE-DEFINING THE STRUCTURE AND FUNCTION OF THE NIGERIA POLICE - Ogaga Ayemo Obaro (European Scientific Journal, ESJ, 2014)
The objective of the paper is to examine the Nigerian Police Force as a colonial institution that has survived for several decades, in order to understand the modifications and adaptations which have occurred in its historical role and functions, especially, after indigenous personnel had replaced the expatriate ones. It is assumed that such adaptations would be able to achieve greater congruence with the values and norms of the Nigerian society. The Nigerian Police Force, surely, has experienced different leadership qualities, training and several reorganizations, including purging it of the ‘bad eggs’. But how near is the nation to a sufficiently friendly, responsive, literate, largely honest, well-equipped, numerically adequate and efficient police force that is able to sustain public confidence in any appreciable sense? The paper argues that a meaningful inquiry into the historical evolution of the role and functions of the Nigeria Police would be a helpful analytical framework with which to deal with the crisis of confidence in the Nigeria Police Force. The paper affirms that there can be a ‘good’ Nigeria Police Force which can achieve institutional significance and endear itself to the collective popular psyche.